The Impact of Circular Economy Practices on Manufacturing Competitiveness in Global Markets - Gabriela, Ilie; Nicolae, Nicolae (Cebong Journal, 2025)
This research investigates the impact of circular economy (CE) practices on the competitiveness of manufacturing firms in global markets. The study highlights how strategies such as resource efficiency, waste reduction, product life-cycle extension, and closed-loop systems contribute to cost efficiency, innovation, and long-term resilience. By analyzing relevant literature and industry practices, the research demonstrates that firms adopting CE principles are better positioned to comply with environmental regulations, respond to shifting consumer demand for sustainable products, and mitigate risks associated with resource scarcity. The findings show that CE adoption is no longer a voluntary option but a strategic necessity for enhancing competitiveness in a rapidly globalizing economy. While the results confirm the positive correlation between CE practices and manufacturing performance, challenges remain in ensuring consistent measurement of competitiveness across diverse contexts, addressing variability in adoption across industries and regions, and overcoming data availability constraints. This study contributes to the broader discourse on sustainable industrial development by underlining the role of CE as a transformative driver of both environmental responsibility and global market success.